2021
DOI: 10.21203/rs.3.rs-1036153/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can sarcopenia index serve as a predictor of myocarditis from mRNA based COVID-19 vaccine, insights from clustered cases and potential involvement of micro-RNAs in its pathogenesis.

Abstract: Background: With the current mass international roll out of several vaccines against SARS-Cov-2, several reports of unheeded complications have made headlines. One of which involves myocarditis with the now FDA fully approved vaccine, Pfizer, and others. We hypothesize through this study that a dysregulated micro-RNA response resulting from such type of vaccines can be involved in triggering myocarditis. Methodology: Embase, Medline and the Cochrane Central Register were used to search for specific keywords su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…2528 3136 ). From the search update, we identified 34 new reports across all questions (Q1=9 3745 , Q2=5 37 41 4547 , Q3=1 48 , Q4=3 39 49 50 , Q5=21 9 5170 ); we excluded five studies that only reported on combined myo- and/or pericarditis (as we located other studies with these reported separately), 7175 eight studies that did not report on confirmed cases, 7683 and three studies 8486 that did not contribute additional data to other included studies on the same cases. Tables of study characteristics, with all data on results, and risk of bias ratings for questions 1 and 2 are in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2528 3136 ). From the search update, we identified 34 new reports across all questions (Q1=9 3745 , Q2=5 37 41 4547 , Q3=1 48 , Q4=3 39 49 50 , Q5=21 9 5170 ); we excluded five studies that only reported on combined myo- and/or pericarditis (as we located other studies with these reported separately), 7175 eight studies that did not report on confirmed cases, 7683 and three studies 8486 that did not contribute additional data to other included studies on the same cases. Tables of study characteristics, with all data on results, and risk of bias ratings for questions 1 and 2 are in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
“…We included 21 papers, 9 5170 including narrative reviews, opinion pieces, letters to the editor, case reports, case series, a retrospective study, and a protocol for a prospective observational study. Across the included papers, we identified 16 hypotheses that are presented in Table 7 .…”
Section: Resultsmentioning
confidence: 99%